Comparison between the impact of morning and evening doses of rivaroxaban on the circadian endogenous coagulation rhythm in healthy subjects. (30th January 2016) - Brunner‐Ziegler, S.; Jilma, B.; Schörgenhofer, C.; Winkler, F.; Jilma‐Stohlawetz, P.; Koppensteiner, R.; Quehenberger, P.; Seger, C.; Weigel, G.; Griesmacher, A.; Brunner, M.
Abstract : Essentials It is unknown whether single rivaroxaban doses should best be administered in the morning or evening. Circadian rhythm of coagulation/fibrinolysis was measured after morning or evening intake of rivaroxaban. Evening intake of rivaroxaban leads to prolonged exposure to rivaroxaban concentrations. Evening intake of rivaroxaban better matches the morning hypofibrinolysis. Summary: Background: A circadian variation of the endogenous coagulation system exists with hypercoagulability and hypofibrinolysis and a corresponding peak of cardiovascular thromboembolic events in the morning. So far, no information is given as to whether single daily doses of the new oral anticoagulant drug rivaroxaban should best be administered in the morning or the evening. Materials and methods: Sixteen healthy male or female volunteers with a mean age of 26 ± 7 years were included in this randomized, controlled, analyst‐blinded cross‐over clinical trial. All subjects were given three morning and three evening single doses of 10 mg rivaroxaban. Circadian rhythms of prothrombin fragment 1 + 2, plasminogen activator inhibitor, and plasmin–antiplasmin complex were measured before any medication intake, as well as after morning or evening medication intake. Rivaroxaban concentrations were determined by an anti–activated factor X assay and liquid chromatography–mass spectrometry. Main results: Concentrations of rivaroxaban were higher 12 h after evening intake of rivaroxaban than 12 h after morning intake (53.3 ng mL −1 [95% confidence interval 46.0–67.8] vs. 23.3 ng mL −1 [19.4–29.1, respectively]). Rivaroxaban intake in the evening reduced morning F 1+2 concentrations better at 8:00 AM than did administration on awakening (85 ± 25 nmol L −1 vs. 106 ± 34 nmol L −1, CI: 9.4‐32.1). In addition, this suppression effect was longer lasting after evening intake. Conclusions: Evening intake of rivaroxaban leads to prolonged exposure to rivaroxaban concentrations and better matches the morning hypofibrinolysis. These results might help to further improve the efficacy and safety of rivaroxaban treatment.